Teachers’ Euphemism on Language Learning: Sociolinguistics Study in Higer Education - Amiruddin, Mohammad; Zuhri, Muhammad Darrin; S, Evha Nazalatus, (Journey: Journal of English Language and Pedagogy, 2025)
The goal of this research was to identify the teachers' euphemism language in language learning, as well as the roles of euphemism in supporting students' language learning. This was a qualitative research that used a descriptive case study approach. This qualitative descriptive study explored teachers’ use of euphemism in language learning and examined its role in supporting students’ learning motivation.  This study's participants included students and teachers from Madura University. Data on euphemism and its effects on language development were gathered through observation and interviews. The results of the study showed that there were five euphemisms used by instructors in language learning: (1) outspoken, (2) large boned, (3) curvaceous, (4) distinctive, and (5) exceptional. 25 % of students claim that professors use "outspoken" instead of "bossy", "big boned" instead of "large", "curvy" instead of "fat", "unique" instead of "odd or weird", and "special" instead of "conforming with expectations". Teachers employed euphemisms in language learning to avoid using taboo words, to save pupils from losing face, to reduce students' fear, and to motivate them. According to the student responses, 62.5 % students declared that the usage of euphemism was to avoid taboo words, 12.5  % students believed that it was to prevent losing face of the students, and 12.5 % students’ claimed that it decreased the anxiety level of the students, and 12.5 % students stated that was to inspire the students. It indicated that proper words, phrases, clauses, sentences, and utterances in language acquisition were essential for motivating pupils and creating a meaningful language environment. These findings highlight the importance of polite and motivating linguistic strategies in fostering effective learning interactions in higher education.